(untitled) (Historia, 2021)
Of conferences there is no end: we let off steam and then sinkback in complacency, and in the end nothing is done. It is easier to talkthan to act. The passing of resolutions is only the initial step. A greatdeal of hard work lies ahead of us. ,As I see it history should not be used to promote better understandingbetween groups or nations; history should not be used to serve anypolitical ends no matter how lofty our motives may be; but history shouldbe taught in such a way that misunderstandings do not arise and so thatold prejudices are not reinforced and so that new prejudices are notcreated